2015
DOI: 10.1128/jvi.03351-14
|View full text |Cite
|
Sign up to set email alerts
|

A Basic Cluster in the N Terminus of Yellow Fever Virus NS2A Contributes to Infectious Particle Production

Abstract: The flavivirus NS2A protein is involved in the assembly of infectious particles. To further understand its role in this process, a charged-to-alanine scanning analysis was performed on NS2A encoded by an infectious cDNA clone of yellow fever virus (YFV). Fifteen mutants containing single, double, or triple charged-to-alanine changes were tested. Five of them did not produce infectious particles, whereas efficient RNA replication was detectable for two of the five NS2A mutants (R22A-K23A-R24A and R99A-E100A-R10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
51
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 33 publications
5
51
0
Order By: Relevance
“…Remarkably, an adaptive mutation, K127KK, in NS2B could compensate for the defects in virion assembly, as well as NS2A-NS2B interaction. These results indicate that NS2B participates in virion assembly through interaction with NS2A, a protein known to be important for flavivirus assembly (17)(18)(19)(20). Overall, our data demonstrate, for the first time, that flavivirus NS2B participates in virion assembly.…”
supporting
confidence: 51%
See 3 more Smart Citations
“…Remarkably, an adaptive mutation, K127KK, in NS2B could compensate for the defects in virion assembly, as well as NS2A-NS2B interaction. These results indicate that NS2B participates in virion assembly through interaction with NS2A, a protein known to be important for flavivirus assembly (17)(18)(19)(20). Overall, our data demonstrate, for the first time, that flavivirus NS2B participates in virion assembly.…”
supporting
confidence: 51%
“…NS2A is the first identified NS protein engaged in both processes. Mutations within NS2A of YFV, DENV-2, and the Kunjin subtype of West Nile virus (KUNV) were found to affect viral RNA synthesis and/or the production of infectious particles (18,19,26). Additionally, the second-site mutations in NS3 helicase could compensate for the defect in infectious YFV production caused by NS2A mutations (17,19), which suggested that the genetic interaction between NS2A and NS3 is critical for virion production (17,19).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, mutation of amino acid 190 (K190S) in YFV NS2A had no effect on viral RNA synthesis but blocked the production of infectious virus (24). A basic cluster in the N terminus of YFV NS2A was identified as responsible for infectious-particle production (25). A mutation at amino acid position 59 (I59N) in WNV KUN blocked the production of secreted virus particles but not RNA replication (26).…”
Section: Importancementioning
confidence: 99%